1991
DOI: 10.1055/s-2006-960044
|View full text |Cite
|
Sign up to set email alerts
|

Thein vitroEffects of Griffonin and Ouabain on Erythrocyte Sodium Content Obtained from Normal Subjects and Sickle Cell Patients

Abstract: The in vitro effects of griffonin and ouabain on erythrocyte sodium content have been investigated in 6 normal subjects and 6 sickle cell patients. Intracellular sodium contents of normal or sickle cells incubated for 8 h in tris buffer, griffonin/tris buffer, or ouabain/tris buffer were determined. Incubation of normal cells in tris buffer or 0.5 mmol/l griffonin had little effect on the cell sodium content. However, 1.0 mmol/l griffonin/tris buffer raised the cell sodium level (P less than 0.05) over the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…In vitro studies with red cells from people with SCD have shown potentially clinically beneficial action of extracts of plants, includingFagara xanthyloides (Honig 1975;Osoba 1989), Khaya senegalensis (Fall 1999), Gri onin and Ouabain (Larmie 1991), and Cajanus cajan (Akojie 1992;Ekeke 1985;Iwu 1988;Onah 2002). Unfortunately, progress has been slow and largely guided by anecdotal reports of benefit in single patients, with little in the way of larger trials.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…In vitro studies with red cells from people with SCD have shown potentially clinically beneficial action of extracts of plants, includingFagara xanthyloides (Honig 1975;Osoba 1989), Khaya senegalensis (Fall 1999), Gri onin and Ouabain (Larmie 1991), and Cajanus cajan (Akojie 1992;Ekeke 1985;Iwu 1988;Onah 2002). Unfortunately, progress has been slow and largely guided by anecdotal reports of benefit in single patients, with little in the way of larger trials.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…In vitro studies with red blood cells from people with SCD have shown potentially clinically beneficial action of extracts of plants (Imaga 2013;Vaishnava 2016), including Fagara xanthyloides (Honig 1975;Osoba 1989), Khaya senegalensis (Fall 1999), Gri onin and Ouabain (Larmie 1991), andCajanus cajan (Akojie 1992;Ekeke 1985;Iwu 1988;Onah 2002). Unfortunately, progress has been slow and largely guided by anecdotal reports of benefit in single patients, with little in the way of larger trials.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Il est ubiquitaire de l'Afrique de l'Ouest (Libéria, Côte d'Ivoire, Ghana, Togo) et de l'Afrique centrale (Cameroun et Gabon) (Kim et al, 2009 ;Juliani et al, 2013). Griffonia est utilisé en médecine traditionnelle pour le traitement de plusieurs pathologies (troubles rénaux, ulcérations cutanées, plaies syphilitiques, de la toux, constipation, vomissements, drépanocytose, inflammations) et pour son effet aphrodisiaque (Den Boer et Westenberg, 1990 ;Larmie et Poston, 1991 ;Neuwinger, 2000 ;Brendler et al, 2010 ;Kumar et al, 2010). Au cours des dernières décennies, Griffonia a connu un essor commercial au niveau international grâce à la richesse de ses graines en 5-hydroxytryptophane (5-HTP), un acide aminé rare (Lemaire et Adosraku, 2002).…”
Section: Introductionunclassified